Whole exome sequencing unveils a frameshift mutation in CNGB3 for cone dystrophy: A case report of an Indian family. Issue 30 (July 2017) - Gupta, Shashank; Chaurasia, Amit; Pathak, Ekta; Mishra, Rajeev; Chaudhry, Vidya Nair; Chaudhry, Prashaant; Mukherjee, Ashim; Mutsuddi, Mousumi
Abstract: Rationale: Genetic elucidation of cone-dominated retinal dystrophies in Indian subcontinent is much needed to identify and catalog underlying genetic defects. In this context, the present study recruited a consanguineous Indian family affected with autosomal recessive cone dystrophy (CD). Considering the huge genetic heterogeneity and recessive inheritance of the disease, we chose to dissect out causal variant in this family by whole exome sequencing (WES). Patient concerns: In the recruited family, three of the six siblings had complaints of poor visual acuity, photophobia, and disturbed colour vision since early childhood. Fundus examination disclosed vascular attenuation and macular retinal pigment epithelium (RPE) changes in all the affected siblings, signifying degeneration of photoreceptor cells. Diagnosis: Complete clinical investigation and electroretinography studies led to the diagnosis of cone dystrophy in three siblings of the family. Interventions: Detailed ophthalmic examination, including family history, visual function testing, and retinal imaging, was performed. We captured and sequenced exomes of 2 affected siblings and their mother using SureSelect Human All Exon V5 Kit on Illumina HiSeq 2000/2500 platform with 100 bp paired-end sequencing method. Candidates after data analysis were screened by segregation analysis and Sanger sequencing. Considering recessive inheritance and consanguinity in the pedigree, we attempted to map large loci homozygous by descent in the genome of patients using exome sequencing variants. Extensive protein modeling was carried out to assess possible consequences of the identified variant on the 3-dimensional structure of the protein. Outcomes: WES generated more than 65, 000 variants for each individual. Assuming recessive inheritance, 13, 026 variants were selected. Further filtering on the basis of their position in gene, class, and minor allele frequency constricted the huge list to 12 rare variants. Finally, we ascertained a single base deletion c.1148delC (p.Thr383fs) in the gene CNGB3 as the causal variant. This is a recurrent frameshift mutation resulting in truncated CNGB3 protein. We mapped a large 15-Mb stretch of homozygous markers spanning the causal variant in the proband. The gene CNGB3 encodes modulatory subunit of cyclic nucleotide-gated channels in cone photoreceptors. Protein modeling reveals loss of 2 transmembrane helices and conserved CAP_ED domain in truncated CNGB3, which eventually is predicted to form nonfunctional channels and hamper phototransduction. Lessons: We have identified a recurrent mutation c.1148delC (p.Thr383fs) in CNGB3 for autosomal recessive CD. The present report provides the first description of CNGB3 mutation from India. It is also the foremost investigation of familial CD in Indian patients; therefore, it presents the primary genetic etiology of CD in India. Abstract : Supplemental Digital Content is available in the text